Electrical characterization of novel vertically orientated carbon - Chua, Yong Quan. (2013)
Vertically Oriented Carbon (VOC), a novel material discovered that have many amazing properties. Although the exploration and discovery of the characteristics of this novel material is still at its infancy stage, research has shown that it is the strongest two-dimensional structure known. Not only is VOC thermally and acoustically conductive, its hexagonal crystalline structure allows it to conduct current effectively anisotropic, which is along its plane.